The syntheses of [14C]BMS‐823778 for use in a human ADME clinical study and of [13CD313CD2]BMT‐094817, a stable‐isotope labeled standard of a newly detected human metabolite. (12th May 2016) - Maxwell, Brad D.; Tran, Scott B.; Lago, Michael; Li, Jun; Bonacorsi, Samuel J.
Abstract : Type 2 diabetes is a significant worldwide health problem. To support the development of BMS‐823778 as an inhibitor of 11β‐hydroxysteroid dehydrogenase type 1 for type 2 diabetes, the synthesis of carbon‐14‐labeled material was required for use in a human adsorption, distribution, metabolism, and excretion (ADME) study. The HCl salt form of [ 14 C]BMS‐823778 was synthesized in two steps from commercially available [2‐ 14 C]acetone. The radiochemical purity of the synthesized [ 14 C]BMS‐823778 after dilution with unlabeled clinical‐grade BMS‐823778 was 99.5% having a specific activity of 7.379 μCi/mg. One result of the human ADME study was the detection of a new human metabolite, BMT‐094817. To support the quantification of BMT‐094817 in clinical samples, it was necessary to synthesize [ 13 CD3 13 CD2 ]BMT‐094817 for use as a liquid chromatography/mass spectrometry standard. [ 13 CD3 13 CD2 ]BMT‐094817 was prepared in five labeled steps from [ 13 CD3 ]iodomethane. Abstract : To support the development of BMS‐823778 as an inhibitor of 11β‐hydroxysteroid dehydrogenase type 1 for type 2 diabetes, the synthesis of [ 14 C]BMS‐823778 for use in a human adsorption, distribution, metabolism, and excretion (ADME) study was required. One result of the ADME study was the detection of a new human metabolite, BMT‐094817. [ 13 CD3 13 CD2 ]BMT‐094817 was then prepared for use as a liquid chromatography/mass spectrometry standard.